Elementy rodzime i obce w uzbrojeniu wczesnośredniowiecznym na Śląsku - Wachowski, Krzysztof (Acta Universitatis Lodziensis. Folia Archaeologica, 2001)
The paper is devoted to a profound analysis of elements of early Mediaeval armament. This issue should be treated separately for the period before the year 990 and after, when Silesia became incorporated into the state of Polane. In the first of these phases the picture is quite varied. In the Arms and Armour slight influences of the Slavs, presumably coming from the east, as well as Merovinian and late Avar are visible. Around the year 800 early Carolingian imports appear, although the 9th century at large is characterised by a certain stagnation of cultural contacts in Śląsk. Only at the decline of the century Great Moravian elements appear. The 10th century is the period of old Hungarian and Czech influences. Early Mediaeval armament in Silesia in the period when this district was incorporated into the Piast monarchy is not so strongly culturally differentiated. Western influences are mainly noticeable, although Scandinavian and Russian features are observable as well. On the map illustrating the distribution of militaries in the period of early Piasts emerges their concentration which can be identified with Opolini.